Evaluation of total acid number (TAN) of synthetic ester retrofilled oil and its correlation with FTIR spectroscopy - Othman, N. A.; Zainuddin, H.; Yahaya, M. S.; Azis, N.; Ibrahim, Z.; Musni, M. A. C. (IEEE, 2023)
Retrofilling of an existing mineral oil-immersed transformer with ester oil is an alternative approach to extend the lifespan of transformers. This is associated with the excellent properties of ester oil that has high tolerance to moisture that promotes an advantage to prolong the life of paper insulation. However, the retrofilling process will mix the fresh ester oil with the remaining aged mineral oil in the transformer oil, and eventually affects the performance of the new ester oil. Therefore, it is essential to access the performance of mixed oil in order to detect any signs of oil degradation as a result of retrofilling, prior to transformer energization. In this paper, the total acid number (TAN) and Fourier Transform Infrared (FTIR) spectra were measured and analyzed to assess the condition of mixed aged mineral-synthetic ester oil (AMO/SE). Three different proportions of aged mineral oil (AMO), i.e. 3 %, 5 % and 7 % were prepared to simulate different amount of mineral oil residue in a transformer before being retrofilled with fresh synthetic ester oil. The AMO were prepared through thermally ageing of fresh mineral oil in a vacuum oven at 130°C for 150 hours. Based on the findings, it has been intriguingly discovered that the acid number of the AMO/SE oil has decreased as the percentage of AMO increased in fresh synthetic ester oil. In correlation with FTIR spectra, the present acid concentration of the degradation by-product of the retrofilled AMO/SE oils can be observed in carbonyl stretch region at the wavelength of 1700 – 1800 cm−1.